2013
DOI: 10.1002/ep.11856
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Co‐biodegradation of linear and cyclic naphthenic acids in circulating packed‐bed bioreactors

Abstract: Continuous co‐biodegradation of a linear and three cyclic surrogate naphthenic acids namely octanoic acid, trans‐4‐methyl‐1‐cyclohexane carboxylic acid (trans‐4MCHCA), and cis‐ and trans‐4‐methyl‐1‐cyclohexane‐acetic acids (cis‐4MCHAA and trans‐4MCHAA) at concentrations of 100, 50, and 50 mg/L, respectively, was investigated in two circulating packed‐bed bioreactors. Using different combinations of naphthenic acids in the bioreactor influent effects of loading rate on biodegradation of each compound was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Both the carbon number and spatial arrangement of the carboxylic group influenced the biodegradation rates of the three model NAs. D’Souza et al . found that the acyclic octanoic acid biodegraded the fastest in circulating packed-bed bioreactors followed by trans -4-methyl-1-cyclohexanecarboxylic acid, trans -4-methyl-1-cylcohexaneacetic acid, and cis- 4-methyl-1-cyclohexaneacetic acid; the biodegradation of octanoic acid was not affected by the presence of any of the cyclic NAs.…”
Section: Resultsmentioning
confidence: 99%
“…Both the carbon number and spatial arrangement of the carboxylic group influenced the biodegradation rates of the three model NAs. D’Souza et al . found that the acyclic octanoic acid biodegraded the fastest in circulating packed-bed bioreactors followed by trans -4-methyl-1-cyclohexanecarboxylic acid, trans -4-methyl-1-cylcohexaneacetic acid, and cis- 4-methyl-1-cyclohexaneacetic acid; the biodegradation of octanoic acid was not affected by the presence of any of the cyclic NAs.…”
Section: Resultsmentioning
confidence: 99%
“…A 2014 report by the same group [72] discussed the co-biodegradation of octanoic acid (n = 8, z = 0, MW = 144.21 g mol À1 ), trans-4-methyl-1-cyclohexane carboxylic acid (n = 8, z = À2, MW = 142.2 g mol À1 ), cis-4-methyl-1-cyclohexane acetic acid (n = 9, z = À2, MW = 156.22 g mol À1 ), and trans-4-methyl-1-cyclohexane acetic acid (n = 9, z = À2, MW = 156.22 g mol À1 ), one linear and three monocyclic model NAs, using the circulating packed-bed bioreactor (Fig. 10).…”
Section: Biodegradationmentioning
confidence: 95%
“…Several of the reviewed papers report on cost reduction [73,85,106,108,109], improved energy efficiency [49,53], and higher throughput [70,72,92], characteristics of a process that ultimately determine its industrial applicability. That being said, major strides must be made for many of the proposed technologies to realize its full-scale implementation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%